Congenital Rubella and CNS Defects - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
The University Department of Pediatrics and Child Health, Leeds, and the Department of Microbiology, Hospital for Sick Children, London, collaborated in a study of the time relations between maternal rubella infection in pregnancy and the presence and type of defects in 422 children with confirmed congenital rubella registered in the National Congenital Rubella Surveillance Program at their institutions.